Economic growth The Effect Of Local Original Revenue And General Allocation Funds On The Economic Growth Of Indramayu Regency In 2008-2022 - Sholikhah, Fitrotus; Syaeful Bakhri; Refaldo Fanther; David Audretsch (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
Good economic growth is achieved from the State Budget (APBN) and the Regional Revenue itself. This study aims to determine how big is the impact of Local Original Revenue (PAD) and General Allocation Fund (DAU) on the economic growth of Indramayu Regency from 2008 to 2022. This study used a quantitative approach using secondary data from the Central Statistics Agency (BPS) of Indramayu Regency. Data analysis was performed using multiple linear regression method. The results showed that the variable Local Original Income does not affect the economic growth of the Indramayu Regency. In contrast, the General Allocation Fund variable affects the economic development of Indramayu Regency. Based on test F, the variables of Regional Original Income and General Allocation Fund together affect the economic growth of Indramayu Regency.